If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1s + 2t = -5 Solving 1s + 2t = -5 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-2t' to each side of the equation. 1s + 2t + -2t = -5 + -2t Combine like terms: 2t + -2t = 0 1s + 0 = -5 + -2t 1s = -5 + -2t Divide each side by '1'. s = -5 + -2t Simplifying s = -5 + -2t
| (y/-2)=-10 | | 4x+3y-50=180 | | 4x=5-2y | | 5t^2-5T-360=0 | | -8x-30=2x | | x^2+4-15x+10=2x-2 | | 20x^2+4x-24=0 | | (X^2+3)/(X+2) | | 2(x-3)+x(2-x)=2-x^2 | | 8/3x=16 | | (r/4)-3=7 | | 1/3m+1/6=4/9 | | 2x^2+13=73 | | f(x)=x^4-3x^2+4 | | 84*11/28*2/9 | | -(2x+4)=3x+5 | | 3(2)-5y=1 | | X^2+3/X+2 | | 8x^2-24x-144=0 | | x^2-6xy+8y^2=0 | | 3c*5e= | | 12a^2+15a^3= | | 1/4x+2=5 | | x/-3=12 | | 5-x=3x+4 | | 3(4v+8)=-8v-16 | | 2*x+4=0 | | 35/(c+2)=7 | | 8n+1=0 | | 6=-7x | | -5y^3+5y^2-7y^2+7y=0 | | n^3-n=4n^2-4 |